IMPLEMENTASI PERMENDAGRI NO.72 TAHUN 2020 DALAM PELAKSANAAN PILKADES SERENTAK DI MASA PANDEMI COVID-19 (Studi di Kabupaten Banyuwangi) - Jauhar Nashrullah; Wahyu Miftha Arfansyah (LPPM Universitas Ekasakti Padang, 2022)
One of the regions in Indonesia that has experienced delays in the Pilkades several times due to government policies and regulatory uncertainty is Banyuwangi Regency. After experiencing uncertainty, finally the Simultaneous Pilkades during the COVID-19 Pandemic has a legal umbrella with the presence of Permendagri No. 72 of 2020. In 2021, the Simultaneous Pilkades in Banyuwangi Regency can finally be held. This research will examine how the implementation of Permendagri No. 72 of 2020 in the implementation of the Simultaneous Pilkades in Banyuwangi Regency in 2021. This research combines normative-empirical, normative data that issupported by the addition of data or empirical elements through a statutory approach and a case approach.materials (primary, secondary, tertiary) collected are then analyzed using content analysis methods The results of the study indicate that the follow-up to the presence of Permendagri No. 72 of 2020, the Banyuwangi Regency Government issues the Banyuwangi Regional Regulation No. 13 of 2021 concerning Implementation Guidelines on Guidelines for Election, Appointment, Inauguration and Dismissal of Village Heads, then the Banyuwangi Regent also issued Decree No. 188/72/Kep/429.011/2021 regarding the formation of district election committees and sub-district committees and based on interviews with representatives of several villages that held Pilkades, basically the implementation of Pilkades in the field has implemented the protocol according to the provisions of Perbup No. 188/72/Kep/429.011/2021. 13 of 2021 and Permendagri No. 72 of 2020. So based on the results of the study it can be concluded that the Banyuwangi Regency Government has implemented Permendagri No. 72 of 2020 is in the implementation of Simultaneous Pilkades in their area.